Potential demand estimation of east coast fever vaccines in Makuyu division, Kenya: an application of contingent valuation and conjoint analysis. - Ngugi, I.K. (Egerton University, 2002)
East Coast fever (ECF) is considered the most important livestock disease in Eastern Africa and makes producers unable to realize the potential benefit from the sub-sector. Use of vaccines could effectively control the disease. Given the anticipated benefits of ECF vaccines, this study has assessed their potential demand among farmers from Makuyu Division in Central Province of Kenya. This was achieved through estimation of willingness and ability to pay (W A TP) and analysis of farmer preferences. The Contingent Valuation (CV) method and double-bounded logit model were employed to elicit and model W ATP, while conjoint analysis was used in decomposing farmer preferences regarding the vaccine to purchase. The estimated W ATP for sub-unit was slightly higher than that of the other vaccine, infection and treatment method (ITM). Price was identified as a factor statistically influencing demand for the vaccines at 95% contidence level. The contribution of vaccineattributes to purchase decision in order of decreasing importance were; effectiveness, frequency of administration, reactors and price, hence the need to give priority to non-price factors when designing an ECF vaccine.